EFFECT OF THE FERMENTATION METHOD ON INCREASING THE BIOAVAILABILITY OF IRON AND ZINC IN WHEAT GRAIN PROCESSING PRODUCTS AND POSSIBILITIES FOR OPTIMIZATION (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Wheat is one of the oldest crops in human history and is a major food source in many countries. Although it contains protein, fiber, vitamins and minerals, the bioavailability of micronutrients such as iron (Fe) and zinc (Zn) is relatively low. The main reason for this is the naturally occurring phytate (myo-inositol-hexaphosphate) compounds in wheat grains. Phytates form complex chelates with iron and zinc, making them insoluble in the intestine.